PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PUSKESMAS BERBASIS ELEKTRONIK DI PUSKESMAS AMBAL II KABUPATEN KEBUMEN - Dian Budi Santoso; Dwi Setya Pambudi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Ambal II Public Health Center previously used the electronic-based management information system that has been provided by Kebumen District Health Office trough online system, but the system has many weaknesses, especially related to the length of time in processing the data, the patient's age items are still input manually, and can’t print the patient registration sheet containing social identity data, prescription data and patient diagnosis. In addition, there are obstacles related to ip public that can’t be accessed so the system no longer used. Medical recorders want a more responsive system so patients can be served more quickly. The purpose of this study was to develop new electronic based information system on Ambal II Community Health Center and know the user's acceptance of the system. This study was research and development with prototyping approach. The subjects were medical records officers, doctors, midwives, and nurses of Kebumen Community Health Center. In this research, the identification of user requirements, development and testing of an electronic-based management information systems prototype have been done. Users accepted the prototype even though there are still some shortcomings that need to be fixed.